2022
DOI: 10.1002/aenm.202200403
|View full text |Cite
|
Sign up to set email alerts
|

Strain Engineering of Layered Heterogeneous Structure via Self‐Evolution Confinement for Ultrahigh‐Rate Cyclic Sodium Storage

Abstract: To get a robust architecture for rapid and permanent ion insertion/extraction, various frameworks are constructed, attempting to enhance the high‐rate lifespan. However, uncontrollable structural evolution always results in the structural failure derived from the continuous increasing inner strain during the cycling. Herein, inspired by the nest structure, a stable framework with wave‐like surface morphology and cross‐linked inner configuration is fabricated, which possesses fast ion migration channel and stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…[25] Wang et al achieved high-rate Na + storage by designing "bird's nest" layered heterogeneous (SnFe)S 2 to alleviate the strong structural stress induced by high polarization at large current densities. [22] And the COMSOL simulation demonstrates optimized stress distribution for nest-like structures at high current densities. Furthermore, larger specific surface areas and active sites can be provided through reasonable morphology design, leading to faster charge transfer kinetics.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…[25] Wang et al achieved high-rate Na + storage by designing "bird's nest" layered heterogeneous (SnFe)S 2 to alleviate the strong structural stress induced by high polarization at large current densities. [22] And the COMSOL simulation demonstrates optimized stress distribution for nest-like structures at high current densities. Furthermore, larger specific surface areas and active sites can be provided through reasonable morphology design, leading to faster charge transfer kinetics.…”
Section: Introductionmentioning
confidence: 93%
“…[1][2][3] Zn-based batteries are promising for commercialization due to their high theoretical capacity (820 mAh g −1 ), relatively high Zn binder and the current collector, which will lead to the fading in capacity. [22][23][24] In addition, such stress can also change the reaction driving force and weaken the reaction rate. [24] Hwang et al showed that the Li + diffusion in Fe 3 O 4 films can arouse unexpected strains and cause mechanical and contact failures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, the materials with various sodium storage mechanisms have been researched for sodium ion battery anodes, such as intercalation reactions, conversion-type storage, alloying reactions, and complex reaction types . Among all of the energy storage materials, electrode materials with a multireaction mechanism, especially the conversion-alloying type, express one of the best candidates for SIBs owing to their excellent theoretical capacity (e.g., GeS 2 , SnS 2 , Bi 2 S 3 , Sb 2 S 3 ). , Unfortunately, the practical application of this kind of anode material in SIBs has been restrained by their short lifespan and depressed high-rate properties. , The main reasons for the inferior cycling reversibility of these materials can be concluded as follows: (I) the serious coarsening phenomenon of Me 0 converted from sulfides inevitably reduces the active interface, which is derived from a recrystallization process and generates inner stresses during the conversion reaction, resulting in the irreversibility of the subsequent reactions. (II) The accumulation of Me 0 at the Me 0 and Na 2 S interface originating from the immiscibility of Me 0 and Na 2 S further aggravates the irreversible reaction.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Unfortunately, the practical application of this kind of anode material in SIBs has been restrained by their short lifespan and depressed high-rate properties. 16,17 The main reasons for the inferior cycling reversibility of these materials can be concluded as follows: 18−20 (I) the serious coarsening phenomenon of Me 0 converted from sulfides inevitably reduces the active interface, which is derived from a recrystallization process and generates inner stresses during the conversion reaction, resulting in the irreversibility of the subsequent reactions. (II) The accumulation of Me 0 at the Me 0 and Na 2 S interface originating from the immiscibility of Me 0 and Na 2 S further aggravates the irreversible reaction.…”
Section: ■ Introductionmentioning
confidence: 99%